Morphometric study of fissures of lung with its clinical implications - Sabita Singh; Jeneeta Baa; Arpita Soy; Mamata Sar; Dibya Prabha Bara (Wolters Kluwer Medknow Publications, 2022)
Background: Complete or incomplete fissures divide the lung into lobes. Fissures can also be absent in the lung. Quantitative assessment of the completeness of fissures can be helpful for surgeons and radiologists during invasive procedures related to the lung. Hence, the present study was undertaken to record the extent of completeness of fissures, contour of the fissural surface of lobes, and accessory fissures. Methodology: The present study was done on 78 (right-40 and left-38) formalin-fixed random lung specimens obtained from adult cadavers. Results: Majority of oblique oblique fissures were incomplete (left-60.5% and right-60%). The absence of fissures was mainly seen in horizontal fissures (25%). Quantitative assessment for the degree of pulmonary fissure completeness showed that G0 and G3 were found more in the right oblique fissure (ROF) and horizontal fissure, G1 and G2 more in the left and ROF, respectively. Fissural surface of lower lobe was concave in the upper part and convex in the lower part, whereas fissural surface of middle lobe was convex in the majority of cases. Accessory fissures were found in 21.8%. Azygos fissure was present in two right lungs. A strong correlation was found between the depth of oblique fissure and the thickness of left lung. Conclusion: High frequency of incomplete fissures was found. Accessory fissures were commonly observed in the right lung. A wide range of variations in the completeness of fissures was noticed between the present and previous studies. Hence, surgeons and radiologists should be alert of these variations for surgical planning and interpretation of radiological images.